The Anti-Hitler Coalition: From Enmity to Military Alliance — A Formula for Success - A. Yu. Borisov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
It is unfortunate to note again today that World War II did not end, it continues in the form of the war of memory. Politicians and scholars who stand as ideological successors of collaborators are trying to rewrite the history of those tragic days, to downplay the role of the Soviet Union in the victory over fascism. They try to revive certain political myths, which have been debunked long ago, that the Soviet Union and the Nazi Germany bear equal responsibility for the outbreak of World War II, that the Red Army did not liberate Eastern Europe but ‘occupied’ it. In order to combat these attempts it is necessary to examine once again a turbulent history of the inter-war period and, particularly, the reasons why all attempts to form a united antifascist front had failed in the 1930s, but eventually led to the formation of the anti-Hitler coalition.The paper focuses on a complex set of political considerations, including cooperation and confrontation, mutual suspicions and a fervent desire to ﬁnd an ally in the face of growing international tensions, which all together determined the dynamics of relations within a strategic triangle of the Soviet Union — the United States — Great Britain in the late 1930s and early 1940s. The paper shows how all attempts to establish a collective security system during the prewar period had shattered faced with the policy of appeasement, which allowed the Nazi Germany to occupy much of Europe. Only the Soviet Union’s entry into the war changed the course of the conﬂict and made a decisive contribution to the victory over fascist aggressors. The author emphasizes that at such crucial moment of history I.V. Stalin, F.D. Roosevelt and W. Churchill raised to that challenge, demonstrating realism, common sense and willingness to cooperate. Although within the anti-Hitler coalition there was a number of pending issues, which triggered tensions between the Allies, their leaders managed to move beyond old grievances, ideological diﬀerences and short-term political interests, to realize that they have a common strategic goal in the struggle against Nazism. According to the author, this is the foundation for success of the anti-Hitler coalition and, at the same time, the key lesson for contemporary politicians. The very emergence of the anti-Hitler coalition represented a watershed in the history of the 20th century, which has determined a way forward for the whole humanity and laid the foundations for the world order for the next ﬁfty years.